Expanding the Chemical Space of Tetracyanobuta‐1, 3‐diene (TCBD) through a Cyano‐Diels‐Alder Reaction: Synthesis, Structure, and Physicochemical Properties of an Anthryl‐fused‐TCBD Derivative. Issue 64 (12th October 2021) - Mateo, Luis M.; Sagresti, Luca; Luo, Yusen; Guldi, Dirk M.; Torres, Tomas; Brancato, Giuseppe; Bottari, Giovanni
Abstract: Tetracyanobuta‐1, 3‐diene (TCBD) is a powerful and versatile electron‐acceptor moiety widely used for the preparation of electroactive conjugates. While many reports addressing its electron‐accepting capability have appeared in the literature, significantly scarcer are those dealing with its chemical modification, a relevant topic which allows to broaden the chemical space of this interesting functional unit. Here, we report on the first example of a high‐yielding cyano‐Diels‐Alder (CDA) reaction between TCBD, that is, where a nitrile group acts as a dienophile, and an anthryl moiety, that is, acting as a diene. The resulting anthryl‐fused‐TCBD derivative, which structure was unambiguously identified by X‐ray diffraction, shows high thermal stability, remarkable electron‐accepting capability, and interesting electronic ground‐ and excited‐state features, as characterized by a thorough theoretical, electrochemical, and photophysical investigation. Moreover, a detailed kinetic analysis of the intramolecular CDA reaction transforming the anthryl‐TCBD‐based reactant into the anthryl‐fused‐TCBD product was carried out at different temperatures. Abstract : Tetracyanobuta‐1, 3‐diene (TCBD) is a powerful and versatile electron‐acceptor moiety widely used for the preparation of electroactive conjugates. Here, we expand the chemical space of such moiety through a high‐yielding cyano‐Diels‐Alder synthesis of a novel, thermally‐stable anthryl‐fused‐TCBD derivative which presents intriguing physicochemical properties.